Pivotal Role of IL-22 Binding Protein in the Epithelial Autoregulation of Interleukin-22 Signaling in the Control of Skin Inflammation - Fukaya, Tomohiro; Fukui, Takehito; Uto, Tomofumi; Takagi, Hideaki; Nasu, Junta; Miyanaga, Noriaki; Arimura, Keiichi; Nakamura, Takeshi; Koseki, Haruhiko; Choijookhuu, Narantsog; Hishikawa, Yoshitaka; Sato, Katsuaki (Frontiers in Immunology, 2018)
Disruption of skin homeostasis can lead to inflammatory cutaneous diseases resulting from the dysregulated interplay between epithelial keratinocytes and immune cells. Interleukin (IL)-22 signaling through membrane-bound IL-22 receptor 1 (IL-22R1) is crucial to maintain cutaneous epithelial integrity, and its malfunction mediates deleterious skin inflammation. While IL-22 binding protein (IL-22BP) binds IL-22 to suppress IL-22 signaling, how IL-22BP controls epithelial functionality to prevent skin inflammation remains unclear. Here, we describe the pivotal role of IL-22BP in mediating epithelial autoregulation of IL-22 signaling for the control of cutaneous pathogenesis. Unlike prominent expression of IL-22BP in dendritic cells in lymphoid tissues, epidermal keratinocytes predominantly expressed IL-22BP in the skin in the steady state, whereas its expression decreased during the development of psoriatic inflammation. Deficiency in IL-22BP aggravates psoriasiform dermatitis, accompanied by abnormal hyperproliferation of keratinocytes and excessive cutaneous inflammation as well as enhanced dermal infiltration of granulocytes and γδT cells. Furthermore, IL-22BP abrogates the functional alternations of keratinocytes upon stimulation with IL-22. On the other hand, treatment with IL-22BP alleviates the severity of cutaneous pathology and inflammation in psoriatic mice. Thus, the fine-tuning of IL-22 signaling through autocrine IL-22BP production in keratinocytes is instrumental in the maintenance of skin homeostasis.